Perceptions of teachers and students on the application of testportal for TOEIC practice testing - Dien Novita; Gina Yulistiati; Santy Christinawati (Universitas Islam Malang, 2023)
Assessment has always been an important part of education. However, with the recent advent and popularity of online education, teachers must devise new methods and tools for engaging online learners in examinations. Regrettably, there are limited applications available to be implemented quickly on flexible assessments. The purpose of this study is to discover how teachers and students understand this online assessment program, Testportal, for summative assessment. This is a mixed-method study. Three English teachers and 70 students from three English 1 sessions were recruited and agreed to participate in the study. A closed questionnaire, interviews, and nonparticipatory observation were used to collect data. The findings revealed that teachers' and students' perceptions of the Testportal's use were positive. The biggest obstacles that teachers and students experience when accessing Testportal are slow internet connections and teachers' difficulty in operating digital examinations. The challenges that prohibit language teachers from incorporating technology for assessment objectives originate from a lack of rules for planning, technology training, practice, and school and student equipment. Language instructors with understanding of technology and assistance from related sources should be given the opportunity to put their knowledge into practice, be watched by teacher educators, and receive feedback on their progress. The Testportal provided teachers with up-to-date information regarding online exams that support students' learning processes through dynamic assessment feedback cycles, such as teaching, assessing, and modifying different instructions to fit students' learning needs.